Homer's Odyssey : a reading guide - Power, Henry (Lecturer in English) (Reading guides to long poems., 2011)
A fresh and exciting approach to this great work of classical literatureHenry Power provides an overview of the whole poem with detailed commentary of the crucial moments. Readers are encouraged to consider both the oral origins and the rich literary reception of this early epic whilst responding to core themes within it.Key Features'Teaching the Text' section with fresh ideas and flexible teaching templates that can be adapted to existing course structuresIncludes extensive extracts from the poem accompanied by a headnote, commentary and glossesIncludes an annotated bibliography.